Método de comunicación por posiciónamiento ocular para pacientes afectados con ELA. - Minor, A.; Leija, L.; Muñoz, R.; Mosso, J. L. (Revista Mexicana de Ingenieria Biomedica, 2000)
This work describes the development of a communication system that can be used to increase the patient’s quality life affected by amyotrophic lateral sclerosis. This system uses to establish the communication, the patient’s wish of ocular position, a graphic interface and a cursor to surf through it. In the graphic interface is possible to write phrases and sentences using a virtual keyboard with delete, go on and writing functions will allow establishing a communication between the patient and a physician. The only request for establishing the written communication is the user has of the healthy visual system at least one of his or her eyes.